Effect of truncation on TRPM7 channel activity - Zhuqing Xie; Nashat Abumaria (Channels, 2023)
ABSTRACTTransient receptor potential melastatin-like 7 (TRPM7) is a key player in various physiological and pathological processes. TRPM7 channel activity is regulated by different factors. The effects of cleavage of different domains on channel activity remain unknown. Here, we constructed several TRPM7 clones and explored the effects of truncating the mouse TRPM7 at different locations on the ion channel activity in two cell lines. We compared the clones’ activity with the full-length TRPM7 and the native TRPM7 in transfected and untransfected cells. We also expressed fluorescently tagged truncated clones to examine their protein stability and membrane targeting. We found that truncating the kinase domain induced reduction in TRPM7 channel activity. Further truncations beyond the kinase (serine/threonine rich domain and/or coiled-coil domain) did not result in further reductions in channel activity. Two truncated clones lacking the TRP domain or the melastatin homology domain had a completely nonfunctional channel apparently due to disruption of protein stability. We identified the shortest structure of TRPM7 with measurable channel activity. We found that the truncated TRPM7 containing only S5 and S6 domains retained some channel activity. Adding the TRP domain to the S5-S6 resulted in a significant increase in channel activity. Finally, our analysis showed that TRPM7 outward currents are more sensitive to truncations than inward currents. Our data provide insights on the effects of truncating TRPM7 at different locations on the channel functions, highlighting the importance of different domains in impacting channel activity, protein stability, and/or membrane targeting.